Language Testing Reconsidered - Fox, Janna (Actexpress, 2007)
Language Testing Reconsidered provides a critical update on major issues that have engaged the field of language testing since its inception. Anyone who is working in, studying or teaching language testing should have a copy of this book. The information, discussions, and reflections offered within the volume address major developments within the field over the past decades, enlivened by current "takes" on these issues. The real value of this collection, however, lies in its consideration of the past as a means of defining the future agenda of language testing.